Pedagogy in the Era of the Post-Non-Classical Science - V. L. Benin (Russian State Vocational Pedagogical University, 2015)
The paper considers over again the problem of the low quality of the scientific pedagogic research of the recent time. The author analyses numerous publications concerning the above problem and presents his opinion on the actual reasons for stagnation in the modern national pedagogy. Its crisis is primarily caused by ignoring the complications of the world perception, changing world outlook, as well as by long ago developed but rejected necessity for devising new methodological principles and value- and objective-oriented educational attitudes. The exact forms and methods of professional activity of pedagogic process participants are derived from the definite historically developed complex lying in their foundation. The educational system structure depends on the logic of cultural structure of the related era both from the methodological and organizational viewpoint. However, our pedagogy retains the position of the New Time classical methodology not complying with the non-classical paradigm, all the more so with the post-non-classical science. The demonstrative appeal to synergetics - the attempt of pedagogy to position itself in terms of post-non-classical science - still remains doubtful.Not persisting on the absolute correctness of his position, the author invites teaches and specialists from educational sphere to the scientific discussion to facilitate, even partially, the existing problem solving.